Synthesis and study of bicyclomycin analogs - Maruyama, Lynn K., author; Williams, Robert M., advisor (Colorado State University. Libraries, 1987)
The synthetic utility of a key electrophilic coupling reaction developed in the total synthesis of bicyclomycin was explored in the hope that this methodology could be applied to the synthesis of homologs of this unique antibiotic. The coupling reaction was a carbon-carbon bond forming reaction which utilized an electrophilic glycine anhydride derivative and a trimethylsilylketeneacetal in the presence of a Lewis acid. A number of substituted diketopiperazines were made by this route and their elaboration to bicyclomycin homologs attempted. Carbocyclic bicyclomycin derivatives which lacked the oxygen heteroatom in the bicyclic bridge were synthesized as a complementary series of analogs. Various [2.2.2) and [3.2.2) carbocyclic systems were made containing and lacking the structural functionalities believed necessary for biological activity. The desired structural features were based on proposed mechanisms of action for bicyclomycin. These features included: 1) an OR or SR type leaving group at the C-6 position of the piperazinedione, 2) an olefinic moiety alpha to the leaving group at C-6, 3) secondary (-NH-) amides. Methodology was developed for synthesis of these carbocycles, of particular significance was an intramolecular enolate/epoxide opening reaction which yielded both the [2 .2.2) (178, 182, 184) and [3.2.2) (179, 183, 185) carbocyclic skeletons. The regiochemistry displayed by this reaction could be explained by a consideration of Baldwin's Rules for Ring Closure. Attempted deprotonation at the bridgehead position of these carbocycles proved unsuccessful in achieving heteroatom substitution. Consequently, these bridgehead substituted bicyclic compounds (162, 205) were obtained by functionalization of the C-6 position prior to cyclization. The carbocycles obtained through this synthetic work were submitted for biological testing.
Keywords: Antibiotics -- Synthesis